RISK MANAGEMENT OF FERMENTED COFFEE: A CASE STUDY OF FEROFFEE FERMENTED COFFEE PRODUCT - Fauziyyah Rahmat, Afifah
Indonesian coffee production increases with the increasing trend of coffee consumption. Coffee consumption in Indonesia is predicted to increase by 8.22% annually. Besides Arabica and Robusta, one of Indonesia's most popular types of coffee is Luwak coffee. Kopi Luwak is taken from Luwak digestive coffee beans. The high selling price of civet coffee increases the amount of civet coffee. Luwak Coffee Production is vulnerable to the problem of animal abuse because coffee is not the main food for Luwak. Fermentation comes with an external fermented coffee product that uses microbial isolates from the digestive tract of Luwak. As a biotechnology product, Feroffee's production process has a variety of risks that need to be managed. This study discusses to analyze and discuss the risk management of Feroffee raw material procurement, processing, and marketing. Data is collected through in-depth interviews. Risk analysis is carried out using FMEA (Failure Mode and Securities Analysis) which will produce an RPN (Risk Priority Number), while risk management design uses AHP (Analytical Hierarchy Process). The results of the analysis of raw material procurement obtained 11 risk factors which are grouped into three risk groups, namely the risk of coffee cultivation, the risk of harvesting and post-harvest, and the risk of selling coffee. Risks with the highest RPN (Risk Priority Number) value for raw material procurement are pest control (Plant Pest Organisms), shade tree handling, and crop distribution with overall RPN value consisting of 189, 50, and 30. The selected raw is coffee cultivation technology development with a percentage of 58.3%. Processing risk analysis produces 10 risk factors which are grouped into three categories, namely the risk of raw material contribution, risk of production location, and risk of the production process. Risks with the highest RPN (Risk Priority Number) value in preparation is inoculum preparation (RPN 45), packaging of ready-to-drink coffee (RPN 32), and fermentation process (RPN 24). The risk management strategy chosen is the processing of HR (Human Resources) training with a percentage of 44.5%. There are five risk factors in marketing which are grouped into three risk groups, namely the risk of consumer preferences, the risk of customer satisfaction, and the risk of consumer buying interest. Marketing risk with the highest RPN (Risk Priority Number) value is consumer buying interest, consumer knowledge about products, and customer satisfaction with RPN values received in a row of 160, 140, and 96. with a percentage of 40.7%.